Patient knowledge level on the use of simvastatin: A Descriptive Cross-Sectional Study - Yogi; Yuniharce Kadang (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Cardiovascular diseases (CVDs) remain the leading cause of global mortality, accounting for approximately 20.5 million deaths annually, according to the World Health Organization. Elevated cholesterol is a major modifiable risk factor contributing to atherosclerosis, coronary heart disease, and stroke. In Southeast Asia, the prevalence of hypercholesterolemia continues to rise alongside increasing non-communicable diseases. Optimal statin therapy requires adequate patient knowledge to ensure adherence and prevent inappropriate use. This study aimed to determine the level of patient knowledge regarding the use of simvastatin at a community pharmacy in Makassar, Indonesia. Methods: A descriptive cross-sectional study was conducted from June to August 2024 at Abifayruz Pharmacy. A total of 25 adult patients who had received simvastatin were recruited using incidental sampling. Knowledge was assessed using a 10-item structured questionnaire based on the Guttman scale. Data were analyzed using descriptive statistics, chi-square tests, and binary logistic regression. Effect sizes were reported as odds ratios (OR) with 95% confidence intervals (CI). Statistical significance was set at α = 0.05. Results: Overall, 90% of respondents demonstrated high knowledge. In multivariable analysis, no independent variable was significantly associated with high knowledge (e.g., male sex AOR=1.89; 95% CI: 0.11–31.2; p=0.662). Wide confidence intervals reflected limited precision due to a small sample size. Conclusion: Although overall knowledge was high, specific gaps in long-term adherence and in recognizing adverse effects remain. Strengthening pharmacist-led counseling protocols in community pharmacies may enhance medication literacy and support cardiovascular disease prevention strategies